Agricultural Terraced Areas in the Tuscan Archipelago (Italy): Mapping, Consistency, and Territorial Analysis - Leonardo Conti; Paolo Armanasco; Caterina Sottili; Stefano Camiciottoli; Donato Liberto; Michele Moretta; Alberto Masoni; Enrico Palchetti (Land)
Terraced systems represent a valuable resource, increasing productive areas on steep slopes often unsuitable for cultivation. Over the years, these ecosystems have been recognised as having functions beyond agronomic value, such as hydrogeological, historical-cultural, economic, and biodiversity conservation. This research intends to contribute to mapping the terraced areas of the Tuscan Archipelago to estimate the areas falling within four of the seven islands of the Archipelago. In addition to a quantitative analysis, terraced systems were studied in terms of morphological and anthropic parameters, which may influence their functionality or cultivation abandonment. The analyses were conducted in a GIS environment, using the Tuscany Region Spatial Information Database and georeferenced orthophotos acquired from drone field surveys. Through the spatial analyses, it was possible to identify the distribution of the terraced system concerning parameters such as slope, altitude, aspect, distance from road networks and land fragmentation, providing a key to understanding how these parameters may influence the causes of conservation or abandonment of these fragile landscapes. Analyses of the terraced areas showed that the prevalent slopes are between 10 and 30% and that the altitude is variable depending on the island but predominantly between 0 and 200 m. Exposure was found to be the most heterogeneous parameter, and a strong relationship emerged between the functional abandonment of agricultural terraced areas and the distance from road networks. Furthermore, the land register analysis revealed a high degree of land fragmentation, which complicates the management and conservation of terraced systems.